Study on the Influence of Pore Water Pressure on the Stability of Slope. Issue 4 (September 2019) - Feng, Yan; Zhu, Feng; Li, Senlin; Wu, Ye
Abstract: The influence of pore water pressure on slope stability under water drop and seismic action is studied in this paper, taking an embankment as the research object. The temporal changes of seepage field are analyzed first, and then the stability of dam slope is investigated by coupling the stress field with the seepage field. During the process of water drop, the minimum safety factor of slope stability appears at the moment when it stops falling. The greater the falling speed is, the faster the pore water pressure dissipates, and the smaller the safety factor is. Seismic action stimulates the increase of excess pore pressure, and whether to consider the coupling effect of seismic load and pore pressure change will make the results of stability analysis quite different. The cumulative effect of pore pressure may be the crucial factor of the dynamic instability of two-phase media slopes.